The impact of high-tech industry development on energy efficiency and its influencing mechanisms - Zou, Yanfen; Huang, Meijuan; Xiang, Wenjing; Lu, Linzhuo; Lu, Yuhai; Gao, Jingjing; Cheng, Yang (Frontiers in Environmental Science, 2022)
In responding to climate change, energy efficiency is one of the key factors for sustainable development, where the high-tech industry can play an important role. However, whether the development of high-tech industry impacts energy efficiency as well as the mechanisms behind still remain unclear. Thus, based on the dynamic spatial Durbin model, this study aims to investigate: 1) the impact of high-tech industry development on energy efficiency from three perspectives of high-tech industry development, i.e., scale, productivity, and agglomeration, and 2) the mechanisms behind such impact especially through technological innovation and industrial structure. The results confirm the influence of high-tech industry development on energy efficiency both directly and indirectly. On the one hand, our analysis contributes on the existing body of scientific knowledge by expounding the relationship between scale, productivity, and agglomeration of high-tech industry development and energy efficiency. On the other hand, it further deepens the understanding on such relationship by revealing two underlying mechanisms behind, i.e., through promoting technological innovation, the productivity and agglomeration of high-tech industries can either completely or partially improve energy efficiency, while the scale and agglomeration of high-tech industries can hinder energy efficiency to a certain level through the industrial restructuring. Based on these findings, this paper provides some policy implications, which are believed to facilitate the practices of energy conservation and emission reduction in China.